CLINICAL AND HEMOGLOBIN PROFILE OF MALARIA PATIENTS IN KARITAS HOSPITAL, SOUTHWEST SUMBA, PERIOD OF YEAR 2017 - Johan, Alvin; Natalia, Audrey; Djauhari, William; Effendi, Rambu Farah (Institute of Topical Disease Universitas Airlangga, 2020)
Malaria infections in high endemic areas are not pathognomonic and often show non-specific symptoms. The Southwest Sumba district is a high endemic area of malaria with the annual parasite incidence (API) of 14.48